Twenty-one different avian species identified as possible reservoir of avian influenza virus in Lima Metropolitan Region, Peru, Pacific flyway, South America. - Castro Sanguinetti, Gina Ruth (2022)
Twenty-one different avian species identified as possible reservoir of avian influenza virus in Lima Metropolitan Region, Peru, Pacific flyway, South America.